If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x(2x + 7) = 0 Reorder the terms: 9x(7 + 2x) = 0 (7 * 9x + 2x * 9x) = 0 (63x + 18x2) = 0 Solving 63x + 18x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '9x'. 9x(7 + 2x) = 0 Ignore the factor 9.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(7 + 2x)' equal to zero and attempt to solve: Simplifying 7 + 2x = 0 Solving 7 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 2x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 2x = 0 + -7 2x = 0 + -7 Combine like terms: 0 + -7 = -7 2x = -7 Divide each side by '2'. x = -3.5 Simplifying x = -3.5Solution
x = {0, -3.5}
| 2345x-678=678 | | 5(3-2x)=75 | | 2x^2+13x=24 | | -496=-8(-10x-8) | | -165=5(5x-3) | | 5x+1=7+3x | | 160=-7x-6(2x+5) | | 4(5x+7)+-8=-16 | | 3(x-1)=3x+2 | | 8x+8=8x+12 | | 4r+15=4r+11 | | 4xy*6xy= | | -2(4x+5)-11=-5 | | 2x-2=x+x | | 23x-8-14x=10 | | 2(b+8)-9=9 | | 2x^2=-144 | | 3k^2-11k-20=0 | | (8x^3)(2)= | | -8b+9+6b=3b+14 | | (4xy)(6xy)= | | 1+7=43+x | | 234x-67=56 | | y-2=y+3 | | 4(5x-7)-8x=-5 | | 4xy+6xy= | | 6x+24=12x+14 | | 6x-(4x+7)= | | 5a+4(2a+4)= | | 3y-9y=102 | | 344x-78=78 | | 3x^2+3=6x |